2020
DOI: 10.3390/medicina56120680
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Night Shifts and Risk of Breast Cancer among Nurses: A Systematic Review

Abstract: Background and objectives: The incidence of breast cancer worldwide has increased in recent decades, accounting for 1 in 3 neoplasms in women. Besides, nurses are mainly represented by the female collective, most of them, undertaking working conditions with intensive rotative and night shifts due to the 24-h pace of work of this profession. The objective of this study was to assess the possible relationship between shift work, especially night-time work, and the development of breast cancer among nurses. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Night-shift work negatively impacts health, notably because of circadian rhythms perturbations [ 4 8 ]. Its multiple potential consequences include fatigue, sleep disturbance, an increased risk of cancer, cardiovascular diseases, metabolic syndrome, affective disorders, and impaired cognitive function [ 9 19 ]. Beyond these negative health consequences, night-shift work has also detrimental effects on quality of life [ 20 – 22 ], which closely interacts with perceived health.…”
Section: Introductionmentioning
confidence: 99%
“…Night-shift work negatively impacts health, notably because of circadian rhythms perturbations [ 4 8 ]. Its multiple potential consequences include fatigue, sleep disturbance, an increased risk of cancer, cardiovascular diseases, metabolic syndrome, affective disorders, and impaired cognitive function [ 9 19 ]. Beyond these negative health consequences, night-shift work has also detrimental effects on quality of life [ 20 – 22 ], which closely interacts with perceived health.…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature is controversial, as summarized in Table I , numerous studies have suggested that shift work and the night shift may represent one of the main occupational risks associated with BC ( 35 , 36 , 52 , 58 ).…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%
“…To gather the appropriate information, an online questionnaire was used. The main risk variables related to breast cancer and night work which were used in this investigation were extracted and adapted ad hoc based on other questionnaires found in the scientific evidence [3,11,14,45,46]. The final questionnaire was formed by the 8 sections detailed below.…”
Section: Instrumentmentioning
confidence: 99%